Dermoscopy as a Noninvasive Diagnostic Tool for Hailey-Hailey Disease and Darier Disease - Marta Kurzeja; Adriana Rakowska; Magdalena Jasinska; Olga Warszawik-Hendzel; Małgorzata Olszewska; Lidia Rudnicka (Adis, Springer Healthcare, 2023)
Abstract Introduction Hailey-Hailey disease (HHD) and Darier disease (DD) are rare genetic disorders for which differential diagnosis, especially in less obvious cases, can be difficult. The diagnosis is based on the clinical picture and family history, and is confirmed by histopathologic examination. Dermoscopy is a noninvasive technique that is primarily used at the present time to diagnose skin cancers. However, in the past few years this technique has also been increasingly used as a noninvasive diagnostic tool of inflammatory skin diseases. The aim of the study was to evaluate whether dermoscopy is a useful noninvasive diagnostic tool for HHD and DD. Methods We performed an observational retrospective case series study involving 13 patients with HHD (n = 8) and DD (n = 5). The presence or absence of standardized dermoscopic features of inflammatory diseases (according to International Dermoscopy Society [IDS] guidelines) was assessed in these patients. Results The most distinctive feature of HHD was white clouds separated by pink furrows, visible in all cases (8/8; 100.0%). Another distinctive clue of HHD was the crumbled fabric pattern seen in six patients with HHD (6/8; 75.0%). These dermoscopic findings were not present in patients with DD. The most typical features of DD in the dermoscopic examination was star-like or oval-shaped yellow areas surrounded by whitish halo, visible in all patients (5/5; 100.0%). Another distinctive dermoscopic clue of DD was pinkish homogeneous structureless background, which was present in all patients (5/5, 100.0%). These latter two features were not observed in patients with HHD. Conclusion Dermoscopy reveals distinctive features of HHD and DD, respectively. Therefore, we conclude that dermoscopy can be an excellent complementary noninvasive tool in the diagnostic process of patients with HHD and DD.